The effect of platinum precursor concentrations on chlorine sensing characteristics of platinum nanoparticles-loaded single walled carbon nanotubes - Choi, Sun-Woo; Byun, Young Tae (ELSEVIER SCIENCE BV, 2018)
The correlation between platinum (Pt) functionalization and chlorine (Cl-2) sensing capability in single-walled carbon nanotubes (SWCNTs) was investigated. Utilizing a photoreduction technique via ultraviolet (UV) irradiation, the Pt nanoparticles (NPs) with various diameters of 7-80 nm, which were controlled by Pt precursor concentrations, were successfully functionalized on the sidewalls of SWCNTs. The discrete Pt NP-loaded SWCNTs exhibited significantly enhanced response value (-(Delta R/R-0) x 100 = 33.8%) for 1 ppm Cl-2 at room temperature (25 degrees C) compared with that (no response) of pure SWCNTs. On the other hand, in case of continuous Pt NP-loaded SWCNTs, Cl-2 sensing capabilities were significantly degraded. The Cl-2 sensing capabilities of fabricated sensors tended to correlate with geometric configurations of the catalytic Pt NPs on the sidewalls of SWCNTs, due to differences in the electron pathway. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: IMPRINTED ELECTROCHEMICAL SENSOR; GRAPHENE OXIDE NANOMATERIAL; GOLD NANOPARTICLES; SELECTIVE DETERMINATION; VOLTAMMETRIC SENSOR; GAS SENSORS; MECHANISM; NANOWIRES; NITROGEN; TYROSINE